DIALEKTIKA BAHASA BALI DI DESA CEMPAGA, KECAMATAN BANJAR, KABUPATEN BULELENG: KAJIAN LINGUISTIK KEBUDAYAAN - Ni Made Ari Dwijayanthi; Jaya, Made Suardika; I Nengah Adi Widana; I Gusti Agung Rai Jayawangsa (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2025)
This research reveals, describes and analyzes the dialectical situation of Balinese language varieties in Cempaga Village, Banjar District, Buleleng Regency. There are various unique and interesting things related to language and culture in this area. The dialectical conditions in Cempaga Village are greatly influenced by the local cultural system because Cempaga Village is one of the Bali Aga (original Balinese) villages in the North Bali area which still uses the Ulu Ampad system. The cultural system constructs the language system in Cempaga Village and the two influence each other and give birth to language culture. Language culture is passed down and passed down from generation to generation, which of course makes the richness of this cultural treasure last with its speakers. The dialectical situation is dissected using Austin's pragmatic theory which focuses on the variety of speech and the context of its speakers so as to obtain results in the form of dialectical varieties of the Balinese language in Cempaga Village which are analyzed using qualitative methods and presented in analytical descriptive terms.